PATRIMÔNIO, FORTUNA E ESCRAVIDÃO NOS CAMPOS GERAIS DO PARANÁ (1820-1844) - Oliveira, Mariani Bandeira Cruz (2015)
This research is dedicated to the study of the fortunes of the inhabitants of Vila de Castro, located in the Campos Gerais Paranaense in the firt years of the XIX century. The research was to supply 150 post mortem documents (109 belonging to slave owners), opened in the Vila de Castro, between the years 1820-1844. We sought to identify through equity inventoried wealth in the locality. It is analyzed by means of material life, the houses and what they reveal in terms of the daily lives of societies of the period. It characterized the composition of fortunes watching as the men and women of Castro invested the accumulated capital in the ownership of assets. Then established a heritage of these inventoried profile through categories, from the diversity of inventoried goods. The economic hierarchy fortunately range showed that in that society slaveholding, ownership of land and animals (vacuns and cavalares) characterized the region. It was possible to identify a total of 903 slaves. The average slaves in the documents post mortem in the Vila de Castro during the study period exceeded 8 captive by owners.